Peran Iklim Organisasi Terhadap Perilaku Kerja Inovatif Dengan Perilaku Berbagi Pengetahuan Sebagai Mediasi (Studi Kasus Pada Industry Pariwisata) - Metha Aurum Zukhrufani Ainulisany; Tulus Budi Sulistyo Radikun (Efektor, 2022)
This study aims to examine the predictive role of organizational climate in innovative work behavior (IWB) during the COVID-19 pandemic with knowledge sharing behavior as a mediator between the two. These variables were chosen because they are assumed to have an effect on business continuity in the tourism industry during the pandemic. This research method is a cross-sectional quantitative research on individuals who work in the tourism industry, both government and non-government institutions. The study was conducted on selected sample of 84 employees whose jobs are tourism-related across the country. The Hayes Macro Process mediation test was conducted to test the hypothesis. The results showed that knowledge-sharing behavior plays a significant role in mediating the relationship between organizational climate and innovative work behavior. rIt is suggested that the knowledge sharing behavior does not become a mediator between organizational climate and IWB because of the possibility that it can stand alone as a predictor variable. The process of examining employees' perceptions of their climate and its impact on innovation work behavior takes a relatively long time